Convergence of Capital and Insurance Markets: Consistent Pricing of Index-Linked Catastrophic Loss Instruments - Gatzert, Nadine; Pokutta, Sebastian; Vogl, Nikolai (Journal of Risk and Insurance, 2019)
Index-linked catastrophe loss instruments have become increasingly attractive for investors and play an important role in risk management. Their payout is tied to the development of an underlying industry loss index (reflecting losses from natural catastrophes) and may additionally depend on the ceding company's loss. Depending on the instrument, pricing is currently not entirely transparent and does not assume a liquid market. We show how arbitrage-free and market-consistent prices for such instruments can be derived by overcoming the crucial point of tradability of the underlying processes. We develop suitable approximation and replication techniques and-based on these-provide explicit pricing formulas using cat bond prices. Finally, we use empirical examples to illustrate the suggested approximations.
CRIS-Team WoS Importer:2019-02-27

Evaluating Investments in Renewable Energy Projects under Policy Risks - Gatzert, Nadine; Vogl, Nikolai (Energy Policy, 2016)

Portfolio Optimization with Irreversible Long-Term Investments in Renewable Energy under Policy Risk: A Mixed-Integer Multistage Stochastic Model and a Moving-Horizon Approach - Gatzert, Nadine; Martin, Alexander; Schmidt, Martin; Seith, Benjamin; Vogl, Nikolai (European Journal of Operational Research, 2020)